2022
DOI: 10.1590/fst.49121
|View full text |Cite
|
Sign up to set email alerts
|

(S)-(-)-N-[2-(3-Hydroxy-2-oxo-2,3-dihydro-1H-indol-3-yl)-ethyl]-acetamide inhibits colon cancer growth via the STAT1 pathway

Abstract: S)-(-)-N-[2-(3-Hydroxy-2-oxo-2,3-dihydro-1H-indol-3-yl)-ethyl]-acetamide (EA), a new compound isolated from the plant Selaginella pulvinata, has been identified to possess anti-proliferative effects against SK-mel-110 cells in vitro via upregulating the expression of inhibitor of growth family member 4. The present study aimed to investigate whether EA could exert antitumor effects against colon cancer. The results revealed that EA exerted anti-proliferative effects against a broad spectrum of different types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Many extracts and compounds from plants have good anti-tumor effects (Li et al, 2022a;Li et al, 2022b;Tian et al, 2022). Glioma is a common primary tumor of central nervous system with strong invasion ability, easy to metastasis and recurrence, and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many extracts and compounds from plants have good anti-tumor effects (Li et al, 2022a;Li et al, 2022b;Tian et al, 2022). Glioma is a common primary tumor of central nervous system with strong invasion ability, easy to metastasis and recurrence, and poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that many compounds from plants have good activities in antioxidant, anti-inflammatory, anti-tumor and other aspects (Ha et al, 2022;Khan et al, 2022;Li, et al, 2022;Zhao et al, 2022). Panax ginseng is a traditional medicine used to enhance the immunity, which is therapeutically beneficial in terms of invigorating the Qi, relieving the fatigue, and strengthening the physique (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%